A systematic review of reflective practice questionnaires and scales for healthcare professionals: a narrative synthesis. Issue 1 (2nd January 2021) - Ooi, Su Min; Fisher, Paul; Coker, Siân
ABSTRACT: Reflective Practice (RP) is considered a crucial component of personal and professional learning. RP is regarded as a way that professionals learn from experience to understand and enhance their practice by responding appropriately to self-reflection. Despite playing a crucial role in healthcare settings, there is little agreement on how to assess RP. This study aims to systematically review self-rating instruments that assess RP in healthcare professionals. Peer review articles assessing RP in healthcare professionals using a self-rating instrument, published in English between 1998 and 2018 from PubMed, CINAHL, and PsychInfo databases, were considered for inclusion. Eighteen papers were appraised, the strengths and weaknesses of the measures were discussed in accordance with an adapted critical appraisal checklist. In general, all self-report instruments included in this review were potentially generalisable to healthcare professionals or health science programmes with some adaptation. Given the limited evidence for other measurement scales, the Reflective Questionnaire and Self-Reflection and Insight Scale are recommended for measuring RP within healthcare settings. Future research developing a standardised tool for the review of mixed-method, heterogeneous, questionnaire studies is strongly recommended.